Improving Elementary School Teachers' Understanding of the Implementation of Local Wisdom-Based Animated Learning Media through Socialization Activities - Yanti Arasi Sidabutar; Meliana Br Gultom; Vesy Morayva Sitanggang; Marlina Agkris Tambunan; D. Yuliana Sinaga (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
This study aims to improve elementary school teachers' understanding of the implementation of animated learning media based on local wisdom through socialization activities. This community service (PKM) activity was implemented using a participatory socialization method, which combined interactive lectures, demonstrations, discussions, questions and answers, and mentoring. The results of the activity showed that socialization is an effective strategy for improving teacher competence in understanding the implementation of animated learning media based on local wisdom. Systematic delivery of materials, media demonstrations, and interactive discussions provide opportunities for teachers to build conceptual understanding while gaining practical experience in identifying local cultural potential that can be utilized as learning resources